Study on the Water Use at the Tailwater of Nam Theun 2 Hydropower Station through the Canal of the 3rd Water Gate (Case study: Nongping and Boungbao villages) Nhommalath District, Khammounce Province: https://doi.org/10.69692/SUJMRD100181 - Sakounkhou, Khonesavanh; Inkhamseng, Somphone; Philakoune, Souladeth (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Water management is managed through the Nam Theun 2 hydroelectric project. The project has released water in two parts: 1) Water gates and channels release water into natural streams about 30 km long and can drain 1,200 m3/s; and 2) Releasing through the newly constructed regulating dam to the Xe Bang Fai River directly, with a length of about 27 km, can drain 330 m3/s. According to the length of the channel, there is a built water gate for 5 irrigations. Currently, only 3 water gates have been opened to supply water for production in 9 villages that depend on Nhommalath district, Khammouane province. In order to make the use of water through the channel to the maximum benefit, it can operate together between electricity generation and the actual use of water by the community. In this chapter, we have studied the amount of water flow according to the season through Regulating Dam during the past 11 years. Since 2012 to 2022, we have studied the participation of farmers in the management and use of water within the scope of agricultural land. Through comparing the amount of water flow during the past 11 years, from 2012 to 2022, The amount of water flow through the channel with the lowest flow in December 2022 is equal to 0.0 cubic meters per second caused by the stoppage of the company's electricity production to do various repairs, and the highest flow rate in November 2016 was 318.18 cubic meters per second. The reason is that the project has full production capacity to respond to the electricity buyers. Among them, the annual average flow volume with the lowest value in 2022 is equal to 153.06 cubic meters per second, and the annual average flow volume with the highest value in 2017 is equal to 239.11 cubic meters per second. At the time the company stopped production, it used a backup pump with a suction power equal to 0.083 m3/s, which was installed at 2 points to pump water into the irrigation channel for the people. The company is responsible for all costs, such as fuel for the pump, maintenance of the pump, and the water system from the pump to the channel. Assessment of farmers' participation in water management with topics such as survey participation and data collection, participation in the implementation of four seasonal plans, participation in monitoring and evaluation, and participation in the review of all outputs is at a very satisfactory level ( = 3-3.8), except for the topic of participation in determining water use regulations within the channel, and the flood problems are evaluated at a moderate level ( = 2.4). Because of management, the municipality has appointed a committee and has specific management rules. There has never been a natural disaster in the area in the past, such as a drought or flood.